2015
DOI: 10.1038/cr.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-bound structure of the E. coli multidrug resistance transporter MdfA

Abstract: Multidrug resistance is a serious threat to public health. Proton motive force-driven antiporters from the major facilitator superfamily (MFS) constitute a major group of multidrug-resistance transporters. Currently, no reports on crystal structures of MFS antiporters in complex with their substrates exist. The E. coli MdfA transporter is a well-studied model system for biochemical analyses of multidrug-resistance MFS antiporters. Here, we report three crystal structures of MdfA-ligand complexes at resolutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
216
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(238 citation statements)
references
References 49 publications
12
216
1
Order By: Relevance
“…MdfA also has 12 TMHs and functions in the monomeric form. The K d value of MdfA and chloramphenicol was determined to be 75 M using ITC (32). The binding affinity is lower than the observed affinity between NorM_PS and DAPI in our study.…”
Section: Norm_ps Is a Multidrug/hcontrasting
confidence: 38%
See 1 more Smart Citation
“…MdfA also has 12 TMHs and functions in the monomeric form. The K d value of MdfA and chloramphenicol was determined to be 75 M using ITC (32). The binding affinity is lower than the observed affinity between NorM_PS and DAPI in our study.…”
Section: Norm_ps Is a Multidrug/hcontrasting
confidence: 38%
“…This difference could be due to the dominating binding interaction. In the case of MdfA, the carboxyl side chain of Asp-34 forms two H-bonds with the O4 and O5 hydroxyl groups of chloramphenicol (32), whereas in this study, the high-affinity binding between NorM_PS and DAPI is supposed to be caused by electrostatic interactions.…”
Section: Norm_ps Is a Multidrug/hmentioning
confidence: 90%
“…MdfA is an inner membrane protein associated with drug efflux with 12 transmembrane domains. MdfA is well characterized in E. coli, and structural studies have shown that the very N terminus of the protein faces toward the cytoplasm (46,47). The alignments of MdfA from Y. pseudotuberculosis and E. coli revealed that they had a very high level of similarity (73.3% identity), but the E. coli MdfA does not have an RR motif in the N terminus and the Yersinia MdfA has 6 additional amino acid residues in the N-terminal sequence with an RR motif.…”
Section: Discussionmentioning
confidence: 99%
“…Many small molecules are substrates of MdfA, including neutral compounds such as chloramphenicol (Cm) and thiamphenicol, lipophilic cations such as tetraphenylphosphonium (TPP + ) and ethidium bromide (EtBr), and the zwitterionic drug—ciprofloxacin (Adler and Bibi 2004). Crystal structures of E. coli MdfA (ecMdfA) have recently been reported by our laboratory (Heng et al 2015). Based on the parsed structures of ecMdfA, the key location for the binding of a variety of substrates was determined to be the large central cavity within MdfA, which is lined with mostly hydrophobic residues.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the parsed structures of ecMdfA, the key location for the binding of a variety of substrates was determined to be the large central cavity within MdfA, which is lined with mostly hydrophobic residues. An acidic residue, D34, is also present deep within this cavity, and is proposed to be critical for the binding of certain substrates (Heng et al 2015). Also, the substrate-bound crystal structure of MdfA provided a base for further structural and functional study of other homologous proteins, such as MdtM, another MFS transporter, which share high sequence identity with MdfA (Paul et al 2014).…”
Section: Introductionmentioning
confidence: 99%